Penguatan Karakter Disiplin dan Kemandirian Anak TK melalui Kegitan Pembiasaan Positif - Dini, Fidari Nur; Ningsih, Sulis Dian; Mutiara, Yolanda (Nanggroe: Jurnal Pengabdian Cendikia, 2025)
This community service program aims to strengthen discipline and independence among early childhood learners through the implementation of positive habituation at RA AD-DA’WAH in Kalibening Raya. The program involved 28 children in Group B and applied several methods: modeling, demonstration, gradual guidance, positive reinforcement, and social simulation. Data were collected through pre- and post-observation across seven behavioral development indicators. The results show significant improvements in children’s independence in organizing personal items (35% to 78%), queuing discipline (28% to 71%), understanding of handwashing procedures (39% to 86%), ability to follow instructions (50% to 89%), and responsibility in tidying up learning materials (21% to 89%). Emotional regulation and confidence to perform in front of the class also improved. These findings indicate that structured and consistent positive habituation, supported by a conducive learning environment, effectively strengthens early childhood character formation, particularly in discipline and independence. The program is recommended for replication in other early childhood education institutions.